OPERASIONALISASI SPEKTRUM DISEMINASI MULTI CHANNEL TEKNOLOGI PERTANIAN UNTUK DISEMINASI YANG EFEKTIF - Enti Sirnawati; Muhammad Taufiq Ratule (Forum penelitian Agro Ekonomi, 2020)
Downstreaming information of Indonesian Agency for Agricultural Research and Technology (IAARD) technology is carried out, among others, through the Multi Channel Dissemination Spectrum (MCDS). The SDMC employs various dissemination channels and actors to accelerate technology dissemination. MCDS discussions at the operating level are limited especially on how it contributes to more technology adoption. Referring to the Agricultural Innovation System, an innovation arises due to support of various subsystems ranging from technology providers, carriers, users, markets, policies, and interactions among subsystems. Likewise, the MCDS should be supported by its subsystems for an effective dissemination. This paper aims to contribute ideas on subsystems requirements in the implementation of the MCDS and how these subsystems can drive the delivered technology information to be adopted by users. The supporting subsystems (planning, approaches in the implementation process, policies, infrastructure) for technology implementation are essential in dissemination activities. As a system, MCDS does not only focus on delivering IAARD’s technology information, but the success of technological innovation must be supported by dissemination planning and its subsystems, technology application ecosystem, and interaction between potential users and technology producers.